Morphological ontogeny, distribution and descriptive population parameters of Hermannia reticulata (Acari: Oribatida: Hermanniidae), with comments on Crotonioidea. Issue 1 (2nd January 2017) - Seniczak, Stanisław; Seniczak, Anna; Coulson, Stephen J.
ABSTRACT: The ontogeny is known for few species of the oribatid mite genus Hermannia (Hermanniidae). Here, we present the morphological ontogeny, distribution and some descriptive population parameters of Hermannia reticulata Thorell, 1871 collected from throughout Arctic Svalbard. All instars of Herm. reticulata are stocky, as other species of Hermannia Nicolet, 1855 for which ontogeny is known. They have gastronotal setae of similar form and ontogeny (12 pairs in the larva and 16 pairs in the nymphs and adult) and the same is true of prodorsal setae, except in Herm. reticulata the sensillus is clavate, whereas in the other species it is setiform. In Herm. reticulata, setae of the anal segment are delayed to the tritonymph as in most other studied species, whereas they first appear in the deutonymph in Herm. gibba . Studied species also differ by the number of epimeral setae in the nymphs and adult and the ontogeny of leg setae. Hermannia reticulata is a holarctic species and mainly occurs in the circumpolar region, but in Svalbard it is not common. Juveniles were as abundant as adults, but the density and stage structure varied among vegetation classes and samples, especially in rich moss tundra and bird cliff vegetation, where density was most variable. The morphological ontogeny of Herm. reticulata is compared with some other species of Crotonioidea.